Difference in capacity of physiological integration between two ecotypes of Leymus chinensis underlies their different performance - Zhou, Chan; Zhang, Zhuo; Wang, Zhengwen; Yang, Yunfei (Plant and soil, 2014)
BACKGROUND AND AIMS: Physiological integration can enhance the performance of clonal plants, but whether this differs between ecotypes and whether such difference is underlying their distribution have scarcely been addressed. We aimed to determine whether physiological integration differs between ecotypes and whether an ecotype with a wider distribution shows a greater capacity of physiological integration. METHODS: A garden experiment was conducted with ramet pairs of both ecotypes (grey-green and yellow-green ecotype) of a typical rhizomatous clonal plant, Leymus chinensis, using rhizome connection (connected vs. disconnected) and ecotype as factors. Physiological and biomass features were measured and compared to assess the effects of physiological integration for both ecotypes. RESULTS: Physiological integration enhanced the maximum net photosynthetic rate, apparent quantum efficiency, respiration rate, water use efficiency, and chlorophyll content of ramets no matter whether they were subject to nutrient-poor or -rich soil, as long as they were connected to other ramets. Moreover, such an effect on photosynthetic capacity and water use efficiency was larger for the grey-green ecotype than for the yellow-green ecotype. CONCLUSIONS: The results suggested that grey-green ecotype has significantly greater capacity of physiological integration than yellow-green ecotype, which was assumed to be one of the underlying mechanisms of the wider distribution of the former in nature.